HUBUNGAN RIWAYAT PENYAKIT INFEKSI DENGAN KEJADIAN STUNTING PADA ANAK USIA 12-59 BULAN - Trio Subroto; Linawati Novikasari; Setiawati Setiawati (JKM (Jurnal Kebidanan Malahayati), 2021)
HISTORICAL RELATIONSHIP OF INFECTIOUS DISEASE WITH STUNTING EVENTS IN CHILDREN AGED 12-59 MONTHS  Background:Stunting events in the highest Central Lampung district are in Pubian Sub-District, Kecamanatan Anak Tuha, Seputih Agung Sub-District, and Seputih Raman Sub-District, In Seputih Raman sub-district there are 2 Working Areas of Puskesmas Seputih Raman with 4 villages stunting data obtained as many as 153 children, and Rama Indra Health Center with 5 villages with the number of stunting children as many as 183 childrenPurpose : Known to know the history of infectious diseases with stunting events in children aged 12-59 months Methods : Type of quantitative research, design of analytical survey research with cross sectional approach, population and sample is stuntinng child, sampling technique using purposive sampling. Analysis of univariate and bivariate data using chi square test.Results : Incidence of infection in children aged 12-59 as many as 65 respondents (31.9%) and 139 respondents (68.1%). Stunting incidents, as many as 102 respondents (50%) 102 respondents (50%). P-Value = 0.000 to P-Value <α (0.000<0.05) Conclusion: It can be concluded there is a history of infectious diseases with stunting events in children aged 12-59 months in the Working Area of Rama Indra Kec. Seputih Raman Kab.Lampung Tengah Year 2019. Based on the results and discussions, researchers suggest that health promotion related to the prevention of infectious diseases in children needs to be improved to address the problem of toddler stunting in Rama Indra Health Center Working Area.    Suggestion As input for mothers to provide exclusive breastfeeding and nutritious food as well as maintaining the cleanliness of drinking food and a place to live for many people to avoid stunting. Based on the results and discussion, the researchers suggest that health promotion related to the prevention of infectious diseases in children needs to be improved again to overcome the problems of toddlers. stunting in the working area of Rama Indra Health Center. Keywords : Infection, Stunting, Child 12-59 Months  ABSTRAK Latar Belakang: Kejadian stunting di kabupaten Lampung Tengah tertinggi berada di Kecamatan Pubian, Kecamanatan Anak Tuha, Kecamatan Seputih Agung, dan Kecamatan Seputih Raman, Pada Kecamatan Seputih Raman terdapat 2 Wilayah Kerja Puskesmas yaitu Puskesmas Seputih Raman dengan 4 desa data stunting diperoleh sebanyak 153 anak, dan Puskesmas Rama Indra dengan 5 desa dengan jumlah anak stunting sebanyak 183 anakTujuan: Diketahui mengetahui hubungan riwayat penyakit infeksi dengan kejadian stunting pada anak usia 12-59 bulanMetode: Jenis penelitian kuantitatif, rancangan penelitian survey analitik dengan pendekatan cross sectional, populasi dan sampel adalah anak yang mengalami stuntinng, teknik sampling menggunakan purposive sampling. Analisa data univariat dan bivariat mengguankan uji chi square.Hasil : Kejadian  infeksi pada anak usia 12-59 sebanyak 65 responden (31.9%) tidak infeksi sebanyak 139 responden (68.1%). Kejadian stunting, sebanyak 102 responden (50%) tidak stunting sebanyak 102 responden (50%). P-Value = 0,000 sehingga P-Value <α (0,000<0,05)Simpulan : Ada hubungan riwayat penyakit infeksi dengan kejadian stunting pada anak usia 12-59 bulan  Berdasarkan hasil dan pembahasan maka peneliti menyarankan promosi kesehatan terkait pencegahan penyakit infeksi pada anak perlu ditingkatkan lagi untuk mengatasi permasalahan balita stunting di Wilayah Kerja Puskesmas Rama Indra.Saran Menjadikan masukan bagi ibu untuk memberikan ASI eksklusif dan makanan yang bergizi serta menjaga kebersihan makanan miunuman dan temnpat tinggal bagi banak agar dapat terhindar dari stunting.Berdasarkan hasil dan pembahasan maka peneliti menyarankan promosi kesehatan terkait pencegahan penyakit infeksi pada anak perlu ditingkatkan lagi untuk mengatasi permasalahan balita stunting di Wilayah Kerja Puskesmas Rama Indra. Kata Kunci      : Infeksi, Stunting, Anak 12-59 Bulan